ANALYSIS OF THE VALUE OF NATIONALISM IN LEGO-LEGO DANCE IN LOCAL CONTENT LEARNING IN ELEMENTARY SCHOOLS - Mahmud Abdullah Noho; Nurrohmatul Amaliyah (Jurnal Visipena, 2025)
Traditional culture is an important means of instilling nationalistic values in the younger generation. This study aims to analyze the nationalistic values contained in the traditional Lego-Lego dance culture and describe the application of these values in local content learning at Cokroaminoto 1 Islamic Elementary School in Kalabahi. The research method used is descriptive qualitative with an ethnographic approach. Data were obtained through observation, interviews, and documentation, then analyzed in depth to find the meaning of nationalistic values in each element of the dance. The research involved 1 local content teacher, 1 principal, and 1 class consisting of 30 students as informants. Data analysis used the Miles and Huberman interactive model, which included data reduction, data presentation, and conclusion drawing. The results showed that nationalistic values were strongly reflected in the music and dance components, which were then internalized through contextual learning based on local culture. The implications of this study confirm that the integration of nationalistic values in local content is an effective strategy for teachers to strengthen the nationalistic character of students from an early age. The contribution (novelty) of this study lies in the use of regional arts as a pedagogical medium that not only preserves local culture but also systematically constructs the strengthening of nationalistic character in the context of basic education.